Effectiveness of cognitive-behavioural therapy on glycaemic control and psychological outcomes in adults with diabetes mellitus: a systematic review and meta-analysis of randomized controlled trials - Uchendu, C.; Blake, Holly (Wiley, 2016)
Aim